2015
DOI: 10.1590/0104-6632.20150322s00003342
|View full text |Cite
|
Sign up to set email alerts
|

BIOHYDROGEN FROM CHEESE WHEY TREATMENT IN AN AnSBBR: ACHIEVING PROCESS STABILITY

Abstract: -An AnSBBR (anaerobic sequencing batch reactor containing biomass immobilized on an inert support) with liquid phase recirculation, containing a 3.5 L working volume, treated 1.5 L of cheese whey wastewater in 3 and 4 h cycles at 30 °C to produce biohydrogen. From startup the bioreactor presented process instability. To overcome this problem the following measures were taken, however without success: adaptation of the biomass with uncontaminated easily degradable substrates, pH control at very low levels, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
2
Order By: Relevance
“…CW was stored in a refrigerator at 4 • C. Since the pH of the CW was low, before feeding into the reactor, the pH was adjusted to 7.0 with a solution of 1 M NaOH. CW was not sterilized before being fed into the reactor, since it was previously shown that for stable formation of hydrogen, it is sufficient to ensure the storage of whey at 4 • C [23].…”
Section: Substrates and Inoculatesmentioning
confidence: 99%
“…CW was stored in a refrigerator at 4 • C. Since the pH of the CW was low, before feeding into the reactor, the pH was adjusted to 7.0 with a solution of 1 M NaOH. CW was not sterilized before being fed into the reactor, since it was previously shown that for stable formation of hydrogen, it is sufficient to ensure the storage of whey at 4 • C [23].…”
Section: Substrates and Inoculatesmentioning
confidence: 99%
“…(ii) the filling time or feeding strategy (Albanez et al, 2009;Oliveira et al, 2010); and (iii) the organic load (Massé and Masse, 2000;Damasceno et al, 2007;Friedl et al, 2009;Carvalhinha et al, 2010). Currently, in the literature, there is an increase in the potential application of batch and fed-batch reactors to generate bioenergy (methane and hydrogen) in a broad context in which the wastewater should be treated just as raw material and not as a process waste, with the aim of making it possible to obtain energy from the methane/hydrogen generated (Yang et al, 2008;Bezerra et al, 2011;Manssouri et al, 2013;Bravo et al, 2015;Lovato et al, 2012;Lima et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, o reator AnSBBR com biomassa imobilizada operado em batelada e condição termofílica se mostrou uma configuração indicada para o tratamento da vinhaça. Na literatura atual, é cada vez mais comum a utilização desta configuração de reator na produção de metano ou hidrogênio pela viabilização da produção de bioenergia gerada a partir do tratamento de diversas águas residuárias, como vinhaça, soro, esgoto doméstico, efluente da produção de biodiesel e efluentes industriais (BEZERRA et al, 2009(BEZERRA et al, e 2011OLIVEIRA et al, 2009;LOVATO et al, 2012;ALBANEZ et al, 2016;LIMA et al, 2016).…”
Section: Ajuste Cinético Da Rota Metabólicaunclassified